Training of Trainers (ToT) on the Climate Risk Management in Agriculture (CRMA) University Short Course Curriculum - Grossi, Amanda; Dinku, Tufa; Hansen, James; Belay, Berhanu; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
From December 6-16, a ten-day training of trainers (ToT) targeting agricultural universities in Ethiopia was implemented in Adama, Ethiopia by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School, in close collaboration with the International Livestock Research Institute (ILRI) and the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM). The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 12 agricultural universities from across Ethiopia, as well as representatives from RUFORUM and the African Climate Policy Centre (ACPC), to equip teaching staff with the knowledge and skills they need to implement a new five-chapter short course on the topic of Climate Risk Management in Agriculture (CRMA). This course aims to equip graduate and postgraduate students to access, understand, and incorporate the best-available climate information into their professional activities.